Attenuation of Apoptosis by Telmisartan in Atherosclerotic Plaques of Apolipoprotein E Mice: Evaluation Using Technetium 99m–Annexin A5 - Yan Zhao; Songji Zhao; Yuji Kuge; H. William Strauss; Francis G. Blankenberg; Nagara Tamaki (Molecular Imaging)
Technetium 99m ( 99m Tc)–annexin A5, a marker of ongoing apoptosis, is supposed to be useful in the detection of metabolically active atheroma. The aim of this study was to determine the potential of 99m Tc–annexin A5 for evaluating the therapeutic effects of an angiotensin II receptor type 1 blocker (ARB) (telmisartan) on atherosclerosis. Male apolipoprotein E −/− mice were divided into telmisartan-treated (3 mg/kg/d, n = 10) and control ( n = 10) groups. After 16 to 21 weeks of treatment, 99m Tc–annexin A5 was injected and cryostat sections of aortic tissues ( n = 10–12/aorta) were prepared. The 99m Tc–annexin A5 accumulation level in the plaques was evaluated by autoradiography. Serial sections of the plaques were histologically examined to identify the lesion phenotypes (normal vessels, early lesions, atheromatous lesions, and fibrotic lesions), plaque size, macrophage infiltration levels, and lipid deposition levels. Telmisartan treatment significantly decreased the plaque size (0.05 ± 0.05 vs 0.11 ± 0.08, mm 2 ), macrophage infiltration level (0.02 ± 0.02 vs 0.03 ± 0.02, mm 2 ), lipid deposition level (0.01 ± 0.01 vs 0.02 ± 0.02, mm 2 ), and 99m Tc–annexin A5 accumulation level (1.30 ± 1.09 vs 2.15 ± 1.91, × 10 −6 /g). 99m Tc–annexin A5 accumulation levels in the plaques positively correlated with macrophage infiltration ( r = .69, p < .05) and lipid deposition ( r = .66, p < .05) levels. Apoptosis imaging with 99m Tc–annexin A5 may be useful for evaluating the therapeutic effects of ARBs on atherosclerosis.